2011
DOI: 10.3109/00365548.2011.620000
|View full text |Cite
|
Sign up to set email alerts
|

Swedish nursing and medical students’ high vaccination adherence during the influenza A (H1N1) pandemic 2009: Insights for pandemic preparedness

Abstract: The aim of this study was to analyze Swedish health science student decision-making regarding vaccination against pandemic influenza during a national mass vaccination campaign. A questionnaire was distributed to 430 students during the influenza A (H1N1) pandemic in 2009. The data from medical and nursing students were compared and a multiple logistic regression model was applied to identify items independently associated with the decision to be vaccinated. The overall survey response rate was 90%. More medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Previous studies reported taht several health beliefs were also correlated with vaccine acceptability (i.e. perceived likelihood, perceived severity, perceived vaccine effectiveness, perceived potential vaccine harms) [7,8,[10][11][12][13][14]. In our study, we showed once again that beliefs about the vaccine are associated with vaccination rates.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Previous studies reported taht several health beliefs were also correlated with vaccine acceptability (i.e. perceived likelihood, perceived severity, perceived vaccine effectiveness, perceived potential vaccine harms) [7,8,[10][11][12][13][14]. In our study, we showed once again that beliefs about the vaccine are associated with vaccination rates.…”
Section: Discussionsupporting
confidence: 73%
“…In the study conducted during the influenza A (H1N1) pandemic period, the vaccination rate was reported as 93.2% in medical students and 84.8% in nursing students [11]. Compared to the high acceptance vaccine rate in the previous pandemic, the current COVID-19 vaccines hesitancy rate is unacceptable.…”
Section: Discussionmentioning
confidence: 99%
“…One study was a mixed method using both a survey and interviews [ 183 ]. All studied either medical students alone (n = 5) [ 120 , 178 , 181–183 ] or compared medical students with other health populations (n = 7) including health-care professionals [ 177 ], dental students [ 180 ], nursing students [ 179 ], nursing & midwifery students [ 126 , 129 ], university students [ 184 ], and medical residents [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is also noted that this uptake rate is substantially higher than the seasonal influenza vaccine uptake rate amongst HCW of 16.5% in 2008/9, 26.4% in 2009/10 [9], and even the improved postpandemic levels of 34.7% in the winter season of 2010/11 [16]. Studies in other countries found H1N1 vaccine uptake rates among medical students varied between 8% in Greece [22] to 93% in Sweden [23]. …”
Section: Discussionmentioning
confidence: 99%